The Influence Of Attractive Streamers On Purchasing Decisions With Brand Trust As A Moderating Variable - Masrifah, Ifah; Marasabessy, Nabila Cecilia; Susanty, Ida I Dewa Ayu Raka; Susanto, Sherly Ernawaty; Gentari, Katri (Innovative: Journal Of Social Science Research, 2025)
This research is a qualitative study with an explanatory approach, namely an approach that makes previous research, especially the three studies mentioned above, a stepping stone for the development of the research being carried out. The data used in this study are primary data that researchers obtained through questionnaires on users of the Tiktokshop and Shopee platforms as many as three hundred people with each numbering one hundred and fifty people on each platform. The data used was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that that each hypothesis used in this article can be proven and accepted. This is because the P-Values ​​in this article are below the significance level and are positive. In the hypothesis in this article, the P-Values ​​are at 0.014 below the significance level of 0.05. The meaning of these results is that the more attractive the live streaming, the more viewers will decide to make a purchase. The next hypothesis also shows similar results if the P-Values ​​in this article are positive and below the significance level of 0.05, namely 0.000, which is more significant than direct testing of 0.014. Thus it can be concluded that the first and second hypotheses in this article can be accepted.